2010
DOI: 10.1021/ac9021852
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of AC Frequency on the Electrowetting Behavior of Ionic Liquids

Abstract: This paper presents a study of electrowetting of ionic liquids (ILs) under AC voltages, where nine different ILs (including mono-, di-, and tricationic varieties) with three different AC frequencies (60 Hz, 1 kHz, 10 kHz) were experimentally investigated. The main foci of this study are (i) an investigation of AC frequency dependence on the electrowetting of ILs; (ii) obtaining theoretical relationships between the relevant factors that explain the experimentally achieved frequency dependence; and (iii) a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…A large number of studies have been conducted to investigate the drop behaviors in AC electrowetting [8][9][10][11][12][13][14]. It was found that the AC electrowetting of water and simple electrolytes behaves quite differently from that with the DC voltages [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been conducted to investigate the drop behaviors in AC electrowetting [8][9][10][11][12][13][14]. It was found that the AC electrowetting of water and simple electrolytes behaves quite differently from that with the DC voltages [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The ionic liquid, [BMIM][PF 6 ], has a conductivity of 140 mS/m and viscosity of 450 cP (0.45 Pa s) at 25 °C. 23,24 Its relative permittivity is ~12 at low frequencies (~50–100 kHz). 25 …”
Section: Resultsmentioning
confidence: 99%
“…Use of [bmim][NTf 2 ] has several practical advantages: (i) having negligible or no vapor pressure so that evaporation is not a concern and no special sealing or packaging is needed for the filter (11), (ii) resistance to vibrations and satellite drop formation, particularly compared to water or aqueous electrolytes (3), (iii) a lower viscosity than most ILs so that response times are faster than other ILs (11) (3,11), and (vi) negligible effect of water when compare to other ionic liquids (3,11).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the ∆θ is different for different ILs, i.e., some ILs exhibit higher ∆θ at a given voltage, whereas other ILs show lower ∆θ at the same voltage (3,11,12). Therefore, if one needs a wide tunability range of f c , it is desirable to use the first type of ILs, and for fine-tunability the latter types of ILs are desirable.…”
Section: Resultsmentioning
confidence: 99%